CV. Freezer Teknik Business Strategy Formulation and Proposed Implementation - Raeros, Rangga Tri; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2014)
Abstract. CV. Freezer Teknik is the company which engages in refrigerant industry. In the beginning, they only provide any refrigerant service, such as refrigerator, air conditioner, etc. CV. Freezer Teknik only have one factory that located in Mamuju City, West Sulawesi. Their factory already running for two and half of years, and the sales tends to stagnant. A proper strategy formulation is needed to help CV. Freezer Teknik to overcome their issues and also to expand their business, due to their stagnation.The strategy formulation is started by analyzing the external and internal environment of CV. Freezer Teknik. The Strength, Weakness, Threat and Opportunities or SWOT analysis used to create Internal Factor Analysis Summary, External Factor Analysis Summary, and TOWS Matrix analysis. According to the forecast demand and capacity planning, so the best location for new ice factory is defined. An action plan to implement this strategy is created. The financial projection needed to calculate the feasibility of this project. Then, the time plan created which is contained every activity, the responsible division, and the time plan. The critical success factor, then used to determine every key factor or objectives that should be achieved by each activity.Keyword: Corporate strategy, Ice Block Factory, Fisheries Industry, Quantitative Strategic Planning Matrix (QSPM)